2015
DOI: 10.4168/aair.2015.7.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Exhaled Nitric Oxide Measurements in a Korean Population

Abstract: Nitric oxide (NO) is a biologic mediator of various physiologic functions. Recent evidence suggests the clinical utility of fractional exhaled NO (FeNO) as a biomarker for assessing asthma and other respiratory diseases. FeNO methodologies have been recently standardized by international research groups and subsequently validated in several Korean population studies. Normal ranges for FeNO have been reported for various ethnic groups, and the clinical utility has been widely evaluated in asthma and various res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 100 publications
2
27
0
Order By: Relevance
“…An elevated eNO >35 ppb,15 which is a significantly higher value than that of 95% upper limit of Korean healthy elementary school children,16 was interpreted as having asthma. However, low eNO could not exclude asthma because eNO can vary according to the age, height, weight, gender, the presence of atopy, and the analytic instruments 17. Finally, for those who were between 3 and 5 years of age, typical asthmatic symptoms plus either a positive mAPI or objective measures of asthmatic airways, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…An elevated eNO >35 ppb,15 which is a significantly higher value than that of 95% upper limit of Korean healthy elementary school children,16 was interpreted as having asthma. However, low eNO could not exclude asthma because eNO can vary according to the age, height, weight, gender, the presence of atopy, and the analytic instruments 17. Finally, for those who were between 3 and 5 years of age, typical asthmatic symptoms plus either a positive mAPI or objective measures of asthmatic airways, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Clinically and scientifically, there is considerable interest in eNO measurements. Many recent studies have suggested that eNO is useful as a biomarker for diagnosing asthma and predicting steroid responsiveness in airway inflammatory diseases, such as chronic obstructive pulmonary disease (COPD) .…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that the reference values were obtained from relatively small numbers of studies conducted in Western populations [6, 7]. For FeNO analyses, the potential discrepancy between different ethnic or demographic groups have been suggested (frequently higher in Asians than Caucasians) [11, 14]. That was a motivation that we attempted to determine reference ranges in Korean adults in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, they were asked to avoid medication or food intake which could interfere with the results. They were also instructed to avoid smoking or exercise within one hour before on the day of testing [14]. Then, they inhaled over 2-3 seconds to total lung capacity through NIOX filter, and exhaled as an upper airway pressure of 5-20 cm H 2 O. FeNO was measured during its plateau status at least for 3 seconds.…”
Section: Methodsmentioning
confidence: 99%